Optimization of hindfoot alignment radiography. (June 2017) - Yang, Chonglin; Xu, Xiangyang; Hu, Mu; Wang, Bibo; Zhu, Yuan; Liu, Jinhao
Background: Cobey and Buck described methods to evaluate hindfoot alignment, but it is still unclear which method is better and easier to perform in clinical practice. Purpose: To evaluate the optimal method for radiography of hindfoot alignment. Material and Methods: We randomly selected 50 patients visiting the foot and ankle surgery outpatient department who underwent hindfoot alignment radiography between 1 July and 31 August 2015. Radiographs were taken using both Cobey's and Buck's methods. The patients were divided into three groups by calcaneal inclination angle. We assessed the calcaneotibial angle, calcaneovertical angle, and the distance from the bottom of the calcaneus to the mid-tibial axis. A comparative analysis was performed separately using the t-test. Results: One hundred pairs of data for Cobey's and Buck's methods were obtained. The angles were analyzed separately in valgus, normal, and varus situations. The results showed no significant difference between Cobey's method and Buck's method regardless of any situation ( P > 0.05). Regarding the distance between the bottom of the calcaneus and the mid-tibial axis, the average result of Buck's method was about 1 mm larger than that of Cobey's method in the valgus and normal cases ( P < 0.05), except for varus cases ( P > 0.05). Conclusion: Cobey's and Buck's techniques are the classic and popular hindfoot alignment assessment methods. The use of Buck's technique resulted in a better image with a less technical procedure and less time requirement. It is worthy of being popularized and used routinely for hindfoot radiography.